Pemberdayaan Kesehatan Masyarakat Melalui Pengadaan Fasilitas Cuci Tangan pada Masa Pandemi Covid-19 di Masjid dan Mushala Dusun Montong Are Tengah - Dwi Kartika Risfianty; Indrawati Indrawati (LPPM Universitas Pendidikan Mandalika (UNDIKMA), 2020)
The purpose of community service is to provide education to the people of Montong Are Tengah village about the importance of maintaining cleanliness, one of which is by washing hands with soap and running water to break the chain of covid-19 spread. The method of dedication is to provide hand washing facilities directly to the mosque and mushalla. The hand washing facilities provided are in the form of buckets that are equipped with taps, making it easier for people to wash their hands before and after performing worship at mosques and mushalla. Participants of this service consisted of marbots of mosques and mushalla and the people of Montong Are Tengah village. The conclusion of this community service activity provides education to the people of Montong Are Tengah village about the importance of maintaining cleanliness, one of which is by washing hands with soap and running water to break the chain of covid-19 distribution by providing hand washing facilities for mosques and mushalla in Montong Are Tengah village